The Effect of Early Thyroidectomy on the Course of Active Graves’ Orbitopathy (GO): A Retrospective Case Study - Meyer zu Horste, M.; Pateronis, K.; Walz, M. K.; Alesina, P.; Mann, K.; Schott, M.; Esser, J.; Eckstein, A. K. (Hormone and Metabolic Research, 2016)
The aim of the work was to investigate the effect of early thyroidectomy on the course of active Graves’ orbitopathy (GO) in patients with low probability of remission [high TSH receptor antibody (TRAb) serum levels, severe GO] compared to that of continued therapy with antithyroid drugs. Two cohorts were evaluated retrospectively (total n=92 patients with active GO, CAS≥4). Forty-six patients underwent early thyroidectomy (Tx-group) 6±2 months after initiation of antithyroid drug (ATD) therapy, while ATD was continued for another 6±2 months in the ATD-group (n=46). These controls were consecutively chosen from a database and matched to the Tx-group. GO was evaluated (activity, severity, TRAb) at baseline and at 6 month follow-up. At baseline, both cohorts were virtually identical as to disease severity, activity and duration, as well as prior anti-inflammatory treatment, age, gender, and smoking behavior. At 6 month follow-up, NOSPECS severity score was significantly decreased within each group, but did not differ between both groups. However, significantly more patients of the Tx-group presented with inactive GO (89.1 vs. 67.4%, * p=0.02), and mean CAS score was significantly lower in Tx-group (2.1) than in ADT-group (2.8; * p=0.02) at the end of follow-up. TRAb levels declined in both groups (Tx-group: from 18.6 to 5.2 vs. ATD-group: 12.8–3.2 IU/l, p0=0.07, p6months=0.32). Residual GO activity was lower in Tx-group, associated with a higher rate of inactivation of GO. This allows an earlier initiation of ophthalmosurgical rehabilitation in patients with severe GO, which may positively influence quality of life of the patients.
Keywords: thyroid treatment; thyroidectomy; ATD; course of GO